Impacts of macroeconomic environment and governance quality on the stock market - Lee, Kelvin Yong Ming; Mohamad Jais (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the relationship between governance quality and stock market performance using the annual data from 2008 to 2016 for fourteen developing countries. This study used four different indicators, namely stock market return, stock market volatility, stock market development, and stock market liquidity to reflect the stock market’s performance from various aspects. The study further combined the four indicators and formed a new proxy to reflect overall stock market performance by using principal component analysis. The two-step system of GMM estimation was used to test the impact of the macroeconomic environment and governance quality on stock market performance. Specifically, the results obtained show that banking sector development and governance quality have a significant negative relationship with stock market volatility. Meanwhile, the income level has a significant negative relationship with stock market volatility, development, and liquidity. These results suggest that developing countries should strengthen the position of the banking sector and allows the funds to be channeled into the stock market efficiently. Besides that, developing countries also need to improve their governance quality to attract foreign investors. Several policies shall be implemented by the developing countries to improve governance quality in the aspects of voice and accountability, political stability, government effectiveness, regulatory quality, the rule of law, and control of corruption.